Work with children and youth in Belarusian late protestant communities (1917–1991) - Lisouskaya, Tatsiana V. (Journal of the Belarusian State University. History, 2024)
The principles, forms and methods of work with children and youth used by Evangelical Baptist, Pentecostal, and Seventh-day Adventist communities in Belarus in 1917–1991 are analysed. The active work among the younger generation can be explained by the fact that in 1929 in the BSSR believers under the age of 25 made up 22 % of community members, and in Western Belarus believers under the age of 30 made up 30 % of community members. The specifics of the functioning of political and legal systems on the territory of Western Belarus as part of Poland in 1921–1939 and on the territory of the BSSR until 1939 caused differences in the approaches of local late Protestant communities to work with children and youth. In the BSSR in the 1920–30s, Sunday schools and other forms of religious education were banned, and the possibilities of communities in creating youth organisations were severely limited. At the same time, in Western Belarus, within the framework of the late Protestant movement, work was carried out to institutionalise religious work among young people: youth circles and partnerships were actively created in communities. A systematic approach to the religious education of children and the involvement of young people in the late Protestant movement in Western Belarus made it possible to form the backbone of communities and quickly revive religious work in the post-war period. It is noted that the resumption of legal activities of religious communities in the BSSR in 1945–1946 created conditions for the formation of youth, women’s, missionary and other circles and ministries within the communities. In the context of legislative and administrative restrictions on all forms of work with children and youth in the BSSR in 1945–1991, late Protestant communities were forced to abandon systemic forms and methods of work in favor of illegal youth meetings in churches and meetings in private apartments. So, the involvement of young people in the ranks of communities continued, which laid the foundation for the development of the movement in the context of the democratisation of the political and legal system and the formation of new state-confessional relations in the Republic of Belarus since 1991.
Keywords: youth movement; Evangelical churches; late Protestantism; Baptism; Adventism; religious politics; BSSR; Western Belarus